2008
DOI: 10.1007/s10393-008-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Efficiency of Two Flea Species (Oropsylla tuberculata cynomuris and Oropsylla hirsuta) Involved in Plague Epizootics among Prairie Dogs

Abstract: Plague, caused by Yersinia pestis, is an exotic disease in North America circulating predominantly in wild populations of rodents and their fleas. Black-tailed prairie dogs (Cynomys ludovicianus) are highly susceptible to infection, often experiencing mortality of nearly all individuals in a town as a result of plague. The fleas of black-tailed prairie dogs are Oropsylla tuberculata cynomuris and Oropsylla hirsuta. We tested the efficiency of O. tuberculata cynomuris to transmit Y. pestis daily from 24 to 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 23 publications
1
88
1
Order By: Relevance
“…(Figure 2). These two flea species differ widely in their ability to transmit Yersinia pestis, the causative agent of plague: O. t. cynomuris has more than three times greater transmission efficiency of bubonic plague than O. hirsuta (Wilder et al, 2008b). Perhaps the presence or absence of a specific lineage, such as the Rickettsial lineage studied here, or the difference in community composition variability across flea species accounts for the difference in vector competency.…”
Section: Bacterial Diversity Within Individual Fleasmentioning
confidence: 82%
See 1 more Smart Citation
“…(Figure 2). These two flea species differ widely in their ability to transmit Yersinia pestis, the causative agent of plague: O. t. cynomuris has more than three times greater transmission efficiency of bubonic plague than O. hirsuta (Wilder et al, 2008b). Perhaps the presence or absence of a specific lineage, such as the Rickettsial lineage studied here, or the difference in community composition variability across flea species accounts for the difference in vector competency.…”
Section: Bacterial Diversity Within Individual Fleasmentioning
confidence: 82%
“…In many cases, the spread of disease is mediated through arthropod vectors, and vector competency is a key parameter in epidemiological models. However, there is wide variation in vector competency between species (Eisen et al, 2006(Eisen et al, , 2007aWilder et al, 2008b) and even between individuals of the same species (Wilder et al, 2008a). The underlying causes of these differences are clearly important, and a more thorough understanding of the ecological factors associated with the prevalence and persistence of pathogenic lineages associated with vectors will ultimately help predict and prevent the spread of disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Rocky Mountain spotted fever can be transmitted by several different tick species, including Dermacentor variabilis and Dermacentor andersoni [20]. The sylvatic plague in prairie dogs can be transmitted by multiple flea species (Oropsylla hirsuta and Oropsylla tuberculata cynomuris) and through multiple manners (by blocked fleas and also through transition immediately following an infected blood meal) [28,77,78]. Let N N), where θ is called the Allee threshold (see [29]).…”
Section: Time T: N I (T) = S I (T) + I I (T) + R I (T)mentioning
confidence: 99%
“…Numerous other studies have also found that flea bacterial load does not correlate with transmission. [13][14][15][16][17][18] Given the small infectious does of Y. pestis ( 100 cells), 10,[19][20][21][22] the overall number of Y. pestis bacteria is less important than the ability of a small number of these organisms to invade the mouse. It has been suggested that very small numbers of Y. pestis residing in a flea's proventriculus could cause infection through regurgitation during feeding.…”
mentioning
confidence: 99%